Targeting the mutant PIK3CA gene by DNA‐alkylating pyrrole‐imidazole polyamide in cervical cancer. Issue 3 (21st January 2021) - Krishnamurthy, Sakthisri; Yoda, Hiroyuki; Hiraoka, Kiriko; Inoue, Takahiro; Lin, Jason; Shinozaki, Yoshinao; Watanabe, Takayoshi; Koshikawa, Nobuko; Takatori, Atsushi; Nagase, Hiroki
Abstract: PIK3CA is the most frequently mutated oncogene in cervical cancer, and somatic mutations in the PIK3CA gene result in increased activity of PI3K. In cervical cancer, the E545K mutation in PIK3CA leads to elevated cell proliferation and reduced apoptosis. In the present study, we designed and synthesized a novel pyrrole‐imidazole polyamide‐ seco ‐CBI conjugate, P3AE5K, to target the PIK3CA gene bearing the E545K mutation, rendered possible by nuclear access and the unique sequence specificity of pyrrole‐imidazole polyamides. P3AE5K interacted with double‐stranded DNA of the coding region containing the E545K mutation. When compared with conventional PI3K inhibitors, P3AE5K demonstrated strong cytotoxicity in E545K‐positive cervical cancer cells at lower concentrations. PIK3CA mutant cells exposed to P3AE5K exhibited reduced expression levels of PIK3CA mRNA and protein, and subsequent apoptotic cell death. Moreover, P3AE5K significantly decreased the tumor growth in mouse xenograft models derived from PIK3CA mutant cells. Overall, the present data strongly suggest that the alkylating pyrrole‐imidazole polyamide P3AE5K should be a promising new drug candidate targeting a constitutively activating mutation of PIK3CA in cervical cancer. Abstract : The present study proposes a new promising alkylating PI polyamide, P3AE5K, to target the E545K mutation in PIK3CA. P3AE5K showed high sequence‐specific binding affinity to its target nucleotide sequence, and downregulated the mutant PIK3CA expression and reduced tumor growth in a mouse xenograft tumor model of cervical cancer.